UTILIZING INSTAGRAM AS PEDAGOGICAL TOOLS TO PROMOTE STUDENTS SELF-EFFICACY IN WRITING DESCRIPTIVE IN THE FIRST GRADE OF SENIOR HIGHT SCHOOL - dwi ayu widyawati, Ericha (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2021)
Utilizing Instagram as Pedagogical Tools to Promote Students Self-efficacy in Writing Descriptive in the First Grade of Senior Hight School. Writing is one of the beneficial language skills that can help students to express their idea, show their feeling, and build their critical thinking and knowledge. Descriptive text is one type of writing which as basic writing, students can descript some figures with their own feeling and fact. Most of the students in one of senior hight school in Banyuwangi are lack motivation especially at Self-efficacy on writing descriptive. Self-efficacy is the individual perception of the ability to complete and know what they must do to get their goals. Self-efficacy can be influence by some factor such as experience , comment , etc. This research focus on the utilization of Instagram platform as pedagogical tools to promote students self-efficacy in writing descriptive on the first grade on senior hight school Banyuwangi , the participant consist of 36 students. This research used methodology classroom action research and did two cycle. The result showed that the utilization of Instagram as pedagogical tools to promote students self-efficacy in writing descriptive was complete and succesfull. The data showed that in cycle one 66% (24 students) from 36 can reach the passing grade 70 for writing descriptive text and self-efficacy questionaire. The progress grow 3% from cycle one, in cycle two 69% (25 students) of 36 can reach the passing grade 70 for writing descriptive text and self-efficacy questionaire.